Application of Vacuum in Various Types of Porous Media for Cooling - Kini, Hendrik; wardhana, Wardhana; Nurhuda, M. (Jurnal Teknologi Pertanian, 2006)
Porous media, solid substances with a number of coids through which fluids may flow are effective to transfer heat from the medium to fluid. A research was conducted to assess the effect of vacuum in reducing temperature of various types of porous media. Three different particle types, i.e. Well rounded gravel (smooth surface), 2<f<3.6 mm; Coarse sand, angular surface 3.6<f<5 mm, and Fine sand f<2 mm were packed into a tubular plastic support, respectively, through which water was flown Each of these was treated with vacuum with P of -5, -52, -55, and -56 cm Hg for the well rounded gravel; with P of -42, and -10 cm Hg for the angular coarse sand and P of -40 cm Hg for the fine sand. The ability of lowering the temperature of porous media varied from 5 to 14 centigrade, and the time required were dependant mostly on the types of particles and vacuum levels. The fine sand was unable to reduce the temperature, while the angular coarse sand was able to lower the temperature by les tha 5 centigrade. On the other hand, the well rounded gravel particle with smooth surface was able to lower temperature form 26 oC to 13 oC. The levels of vacuum which determined the flow rates of the air and water passed to the porous media, however, did not show any significant effect to the reduction of temperature. It was found that the particle arrangement configuration in the support, which mostly affect the total surface area as well as the flow rate of air are likely to be the dominant factors in temperature lowering. Keywords:Â Porous media, vacuum, temperature lowering